Analisis Restrukturisasi Kredit Pemilikan Rumah sebagai Solusi Kredit Bermasalah: Studi Kasus Debitur Bank BTN KC Malang - Najwa Febi Kharisma; Mardiana Nur Afni Wijayanti; Rela Rahayu; Yuli Soesetio (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze Mortgage Loan Restructuring (Kredit Pemilikan Rumah/KPR) as a solution for resolving non-performing loans at Bank BTN Malang Branch Office, particularly through the implementation of the Installment Recalculation Scheme (Perhitungan Ulang Angsuran/PUA). This study employed a qualitative approach with an exploratory case study design involving a mortgage debtor under the pseudonym Gaby, who underwent two credit restructurings in 2021 and 2026. Data were collected through in-depth interviews, observation, and documentation at the Cluster Loan Quality (CLQ) unit of Bank BTN Malang Branch Office. The results show that credit restructuring plays an important role in resolving non-performing loans by considering the debtor’s repayment capacity, restructuring history, age, and remaining loan period. The first restructuring in 2021 was conducted proactively through a combination of PUSP, PUST, and Grace Period schemes, which successfully restored the debtor’s loan status to current. Meanwhile, the second restructuring in 2026 applied the PUA scheme because it was considered more suitable for the debtor’s financial condition without extending the loan maturity period. This study concludes that restructuring, particularly the PUA scheme, can be an effective solution for handling non-performing loans when implemented based on the debtor’s profile and repayment ability.